Clinical Impact and Prognostic Role of Triglyceride to High-Density Lipoprotein Cholesterol Ratio in Patients With Chronic Coronary Syndromes at Very High Risk: Insights From the START Study - De Luca, Leonardo; Temporelli, Pier Luigi; Colivicchi, Furio; Gonzini, Lucio; Fasano, Maria Luisa; Pantaleoni, Massimo; Greco, Gabriella; Oliva, Fabrizio; Gabrielli, Domenico; Gulizia, Michele Massimo (Frontiers in Cardiovascular Medicine, 2022)
Background Several studies have reported that the combination of high TG and low HDL-C, as simplified by the TG/HDL-C ratio, was a predictor of cardiovascular disease independent of LDL-C level. Nevertheless, poor data are available on the predictive role of TG/HDL-C ratio in very high risk (VHR) patients with chronic coronary syndromes (CCS). Methods Using the data from the STable Coronary Artery Diseases RegisTry (START) study, an Italian nationwide registry, we assessed the association between the TG/HDL-C ratio and baseline clinical characteristics, pharmacological treatment, and major adverse cardio-cerebrovascular events (MACCE) at 1 year in a large cohort of CCS patients at VHR. Results VHR patients with both TG and HDL-C levels available were grouped in tertiles of TG/HDL-C ratio: low (TG/HDL-C ratio <2, n = 967), middle (TG/HDL-C ratio 2–3.3, n = 1,071) and high (TG/HDL-C ratio >3.3, n = 1,028). At 1 year from enrolment, 232 (7.6%) patients presented a MACCE, with a higher incidence in the higher tertile, even though not statistically significant (6.0, 8.2, and 8.4% in the low, middle and high tertile, respectively; p = 0.08). At multivariable analysis, the TG/HDL-C ratio in tertiles did not result an independent predictor of the MACCE (p = 0.29) at 1-year follow-up (HR: 1.30; 95% CI: 0.93–1.82; p = 0.12 middle vs. lower tertile, and HR: 1.22; 95% CI: 0.87–1.72; p = 0.25 higher vs. lower). Conclusions In the present large, nationwide cohort of CCS patients at VHR a high TG/HD ratio did not emerge as independent predictor of MACCE at 1 year. Further studies with a longer follow-up are needed to better define the prognostic role of TG/HDL ratio in CCS.